Phenotypic Differences Between Polygenic and Monogenic Hypobetalipoproteinemia. Issue 1 (January 2021) - Rimbert, Antoine; Vanhoye, Xavier; Coulibaly, Dramane; Marrec, Marie; Pichelin, Matthieu; Charrière, Sybil; Peretti, Noël; Valéro, René; Wargny, Matthieu; Carrié, Alain; Lindenbaum, Pierre; Deleuze, Jean-François; et al.
Abstract : Objective: Primary hypobetalipoproteinemia is characterized by LDL-C (low-density lipoprotein cholesterol) concentrations below the fifth percentile. Primary hypobetalipoproteinemia mostly results from heterozygous mutations in the APOB (apolipoprotein B) and PCSK9 genes, and a polygenic origin is hypothesized in the remaining cases. Hypobetalipoproteinemia patients present an increased risk of nonalcoholic fatty liver disease and steatohepatitis. Here, we compared hepatic alterations between monogenic, polygenic, and primary hypobetalipoproteinemia of unknown cause. Approach and Results: Targeted next-generation sequencing was performed in a cohort of 111 patients with hypobetalipoproteinemia to assess monogenic and polygenic origins using an LDL-C-dedicated polygenic risk score. Forty patients (36%) had monogenic hypobetalipoproteinemia, 38 (34%) had polygenic hypobetalipoproteinemia, and 33 subjects (30%) had hypobetalipoproteinemia from an unknown cause. Patients with monogenic hypobetalipoproteinemia had lower LDL-C and apolipoprotein B plasma levels compared with those with polygenic hypobetalipoproteinemia. Liver function was assessed by hepatic ultrasonography and liver enzymes levels. Fifty-nine percent of patients with primary hypobetalipoproteinemia presented with liver steatosis, whereas 21% had increased alanine aminotransferase suggestive of liver injury. Monogenic hypobetalipoproteinemia was also associated with an increased prevalence of liver steatosis (81% versus 29%, P <0.001) and liver injury (47% versus 0%) compared with polygenic hypobetalipoproteinemia. Conclusions: This study highlights the importance of genetic diagnosis in the clinical care of primary hypobetalipoproteinemia patients. It shows for the first time that a polygenic origin of hypobetalipoproteinemia is associated with a lower risk of liver steatosis and liver injury versus monogenic hypobetalipoproteinemia. Thus, polygenic risk score is a useful tool to establish a more personalized follow-up of primary hypobetalipoproteinemia patients. Abstract : Supplemental Digital Content is available in the text.